SMART THEACING WITH AI IN LEARNING DEVELOPMENT - Juli Azmi; Zainal Efendi Hasibuan; Annisa Hilda Panjaitan; Rika Andriyani Ritonga (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The rapid digital transformation in education has redefined the role of teachers, necessitating the integration of Artificial Intelligence (AI) to enhance pedagogical efficiency. This study aims to analyze the needs of primary school teachers regarding AI, describe the implementation of AI-assisted smart teaching training, and evaluate its impact on teachers' professional competence and the quality of produced instructional tools. Utilizing a descriptive qualitative approach with a field study design, the research was conducted at UPTD SD Negeri 33 Bangai. Data were collected through participatory observation, semi-structured interviews, and document analysis of teaching modules and worksheets. The subjects were selected via purposive sampling, and data were analyzed using the interactive model of reduction, display, and conclusion drawing. The results indicate that AI-assisted smart teaching training effectively shifts teachers from passive technology users to active pedagogical designers. Findings reveal a paradigm shift where teachers perceive AI as "augmenting intelligence" that strengthens rather than replaces their professional role. The instructional tools produced post-training showed significant improvements in systematic alignment and the integration of Higher-Order Thinking Skills (HOTS). Grounded in adult learning and experiential learning theories, this practice-based model fosters greater learning autonomy and reflective practice. This study contributes empirical evidence for the primary education context, suggesting that human-centered and pedagogically-driven AI integration is a vital strategy for teacher professional development in the digital era.